Science and principles of biodegradable and bioresorbable medical polymers materials and properties - Zhang, Xiang 1941- (Woodhead publishing series in biomaterials, 2017)
Science and Principles of Biodegradable and Bioresorbable Medical Polymers: Materials and Properties provides a practical guide to the use of biodegradable and bioresorbable polymers for study, research, and applications within medicine. Fundamentals of the basic principles and science behind the use of biodegradable polymers in advanced research and in medical and pharmaceutical applications are presented, as are important new concepts and principles covering materials, properties, and computer modeling, providing the reader with useful tools that will aid their own research, product design, and development. Supported by practical application examples, the scope and contents of the book provide researchers with an important reference and knowledge-based educational and training aid on the basics and fundamentals of these important medical polymers.--Provided by publisher.